Molecular typing methods for outbreak detection and surveillance of invasive disease caused by Neisseria meningitidis, Haemophilus influenzae and Streptococcus pneumoniae, a review - Harrison, O; Brueggemann, A; Caugant, D; van der Ende, A; Frosch, M; Gray, S; Heuberger, S; Krizova, P; Olcen, P; Slack, M; Taha, M; Maiden, M (Society for General Microbiology, 2011)
Invasive disease caused by the encapsulated bacteria Neisseria meningitidis, Haemophilus influenzae and Streptococcus pneumoniae remains an important cause of morbidity and mortality worldwide, despite the introduction of successful conjugate polysaccharide vaccines that target disease-associated strains. In addition, resistance, or more accurately reduced susceptibility, to therapeutic antibiotics is spreading in populations of these organisms. There is therefore a continuing requirement for the surveillance of vaccine and non-vaccine antigens and antibiotic susceptibilities among isolates from invasive disease, which is only partially met by conventional methods. This need can be met with molecular and especially nucleotide sequence-based typing methods, which are fully developed in the case of N. meningitidis and which could be more widely deployed in clinical laboratories for S. pneumoniae and H. influenzae.